Dampak Fintech Terhadap Perkembangan Inklusi Keuangan Pada UMKM Di Jawa Timur - Mega Arisia Dewi (Universitas Gorontalo, 2020)
This study aims to determine how much influence fintech (risk and investment management, market provisioning, and cashless society) on financial inclusion (financial knowledge, financial behavior, and financial attitudes) on MSMEs in East Java. Research conducted includes the type of quantitative research. The population of this research is 80 MSME industries in East Java, where the data will be used more focused on archival methods available at BPS East Java. This study uses the dependent variable, Financial Inclusion, which consists of: financial knowledge, financial behavior and financial attitudes with independent variables, namely financial technology (risk and investment management, market provisioning, and cashless society). The conclusion of this study is the fintech variable (risk and investment management and market provisioning) does not affect financial inclusion (financial knowledge) while the fintech variable (cashless society) influences financial inclusion (financial knowledge); The fintech variable (risk and investment management and market provisioning) does not affect financial inclusion (financial behavior) while the fintech variable (cashless society) influences financial inclusion (financial behavior); The fintech variable (risk and investment management and market provisioning) does not affect financial inclusion (financial attitude) while the fintech variable (cashless society) influences financial inclusion (financial attitude). Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh fintech (risk and investment management, market provisioning, dan cashless society) terhadap inklusi keuangan (pengetahuan keuangan, perilaku keuangan, dan sikap keuangan) pada UMKM di Jawa Timur. Penelitian yang dilakukan termasuk jenis penelitian kuantitatif. Populasi penelitian ini adalah industri UMKM se-Jawa Timur sebanyak 80 UMKM yang mana data akan digunakan lebih berfokus kepada data arsip (archival method) yang tersedia di BPS Jawa Timur. Penelitian ini menggunakan variabel dependen yaitu Inklusi Keuangan, yang terdiri dari: pengetahuan keuangan, perilaku keuangan dan sikap keuangan dengan variabel independennya, yaitu financial technology (risk and investment management, market provisioning, dan cashless society). Kesimpulan dari penelitian ini adalah Variabel fintech (risk and invesment management serta market provisioning) tidak berpengaruh terhadap inklusi keuangan (pengetahuan keuangan) sedangkan Variabel fintech (cashless society) berpengaruh terhadap inklusi keuangan (pengetahuan keuangan); Variabel fintech (risk and invesment management serta market provisioning) tidak berpengaruh terhadap inklusi keuangan (perilaku keuangan) sedangkan Variabel fintech (cashless society) berpengaruh terhadap inklusi keuangan (perilaku keuangan); Variabel fintech (risk and invesment management serta market provisioning) tidak berpengaruh terhadap inklusi keuangan (sikap keuangan) sedangkan Variabel fintech (cashless society) berpengaruh terhadap inklusi keuangan (sikap keuangan).